Monkeypox - A Review - Hussain, Ijaz; Shaukat, Shehla; Butt, Ghazala (Nepal Journal of Dermatology, Venereology & Leprology, 2023)
The recent past emergence of pandemics has made the world prepare for all the worst-case scenarios. First COVID-19 pandemic caught us unaware, and since then, diseases like Dengue and Monkeypox are making us take steps to avert the casualties caused by these infections. Monkeypox is a viral disease caused by orthopoxvirus. It spreads from close personal contact with the patient. The disease is severe among children, pregnant, and immunosuppressed patients. Recent outbreak among MSM group has added it to be amongst sexually transmitted infections. It is usually self-limiting, but severe disease-causing deaths have been reported by infection, particularly with central African types. Prevention is possible by vaccination with smallpox vaccines. Treatment is still evolving, with new drugs like Tecoviramet showing promising results. Key words: Monkeypox; Orthopoxvirus; Sexually transmitted infection; Tecoviramet